How do i participate in T‐cell immunotherapy?. Issue 5 (5th April 2017) - Suhoski Davis, Megan M.; McKenna, David H.; Norris, Philip J.
Abstract : T cells play a key role in the adaptive immune response, and the ability to manipulate T cells for therapeutic uses has advanced in the past decade. Infusion of expanded or engineered T cells can potentially be used to treat cancer, viral infections, graft‐versus‐host disease, and organ transplant rejection. The role that blood banks play in the manufacture and distribution of T‐cell therapeutics is still being defined. Given the regulatory framework of blood banks, they are well positioned to collect raw material for manufacture of T‐cell therapies and to distribute finished product to hospitals in support of clinical trials or eventually for licensed products. A deeper level of involvement in manufacture of T‐cell therapeutics is also possible, although that requires more substantial investment in physical facilities and personnel with the regulatory and scientific expertise to prepare and produce cellular therapy products. Examples of physical infrastructure needed would be a laboratory with a clean room for culture of T cells, specialized equipment for expansion of the cells, and adequate administrative and storage support space. Processes that would need to be developed to produce T‐cell therapeutics would include development of standard operating procedures and an appropriate quality assurance program. As blood banks consider supporting this novel class of therapies, they will need to weigh capital and expertise requirements with the benefits of providing a novel therapy and the potential of growth for their operations.